Different Current Intensities of Anodal Transcranial Direct Current Stimulation Do Not Differentially Modulate Motor Cortex Plasticity - Dawson J. Kidgell; Robin M. Daly; Kayleigh Young; Jarrod Lum; Gregory Tooley; Shapour Jaberzadeh; Maryam Zoghi; Alan J. Pearce (Neural Plasticity)
Transcranial direct current stimulation (tDCS) is a noninvasive technique that modulates the excitability of neurons within the motor cortex (M1). Although the aftereffects of anodal tDCS on modulating cortical excitability have been described, there is limited data describing the outcomes of different tDCS intensities on intracortical circuits. To further elucidate the mechanisms underlying the aftereffects of M1 excitability following anodal tDCS, we used transcranial magnetic stimulation (TMS) to examine the effect of different intensities on cortical excitability and short-interval intracortical inhibition (SICI). Using a randomized, counterbalanced, crossover design, with a one-week wash-out period, 14 participants (6 females and 8 males, 22–45 years) were exposed to 10 minutes of anodal tDCS at 0.8, 1.0, and 1.2 mA. TMS was used to measure M1 excitability and SICI of the contralateral wrist extensor muscle at baseline, immediately after and 15 and 30 minutes following cessation of anodal tDCS. Cortical excitability increased, whilst SICI was reduced at all time points following anodal tDCS. Interestingly, there were no differences between the three intensities of anodal tDCS on modulating cortical excitability or SICI. These results suggest that the aftereffect of anodal tDCS on facilitating cortical excitability is due to the modulation of synaptic mechanisms associated with long-term potentiation and is not influenced by different tDCS intensities.